2020
DOI: 10.1097/j.pain.0000000000001952
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of chronic pain clinical trial outcomes: IMMPACT recommended considerations

Abstract: IMMPACT meeting and were not employed by industry or government at the time of the meeting received travel stipends, hotel accommodations, and meals during the meeting provided by ACTTION. ACTTION has received research contracts, grants, or other revenue from the FDA, multiple pharmaceutical and device companies, philanthropy, and other sources. Preparation of background literature reviews and the article was supported by ACTTION. No funding from any other source was received for the meeting, nor for the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 107 publications
0
75
0
2
Order By: Relevance
“…Once a trial has been completed and the data analyzed, careful interpretation of the results is necessary. 187 To adequately evaluate the evidence of efficacy provided by a statistically significant primary analysis, several issues must be addressed. Foremost among these are whether the analysis that tested the primary hypothesis of the trial was prespecified and whether the possibility that multiple outcomes or analyses could have inflated the probability of a type I error and was addressed in a satisfactory manner.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once a trial has been completed and the data analyzed, careful interpretation of the results is necessary. 187 To adequately evaluate the evidence of efficacy provided by a statistically significant primary analysis, several issues must be addressed. Foremost among these are whether the analysis that tested the primary hypothesis of the trial was prespecified and whether the possibility that multiple outcomes or analyses could have inflated the probability of a type I error and was addressed in a satisfactory manner.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…5 ). 79 , 187 However, if the confidence interval includes a clinically meaningful effect, then the trial results should be considered inconclusive and as providing the basis for further study to examine the treatment's hypothesized efficacy. 88 Although biostatisticians have advocated this approach to interpreting nonsignificant results of clinical trials for many years, a recent review of RCTs published in general medical journals found that reporting and interpretation of confidence intervals was often problematic.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 articles on prevention and phenotyping that appear at the end of this section of the ACTTION Guide are based on IMMPACT meetings, as are 2 other recent articles on the conduct of analgesic trials and data quality 22 and the interpretation of chronic pain clinical trial outcomes. 56 There are other IMMPACT articles in preparation that present recommendations for clinical trials of opioid sparing, spinal cord stimulation, and visceral and pelvic pain, as well as for benefit-risk evaluation and reporting in chronic pain trials, which when published will provide important complementary information to the articles in the ACTTION Guide. In the following sections, we briefly discuss 3 other forthcoming IMMPACT efforts that reflect important developments in clinical research that are occurring across many different therapeutic areas and that are of great relevance for pain treatments.…”
Section: Trials Transitions and Translationsmentioning
confidence: 99%
“…It is beyond the scope of this brief article to discuss the many other important issues involved in improving the rigor and reproducibility of clinical trials of pain treatments; these issues require attention not only by those who conduct clinical research but also by those who seek to apply the results in clinical practice. Specific recommendations for the preparation and review of publications of pain clinical trials can be found in Gewandter et al, 24 and many of the other articles in the ACTTION Guide and recent publications 22 , 34 , 56 describe additional approaches to reducing bias in clinical trials of pain treatments and ensuring that the results are as informative as possible.…”
Section: Discerning Hype From Substancementioning
confidence: 99%